Budi, knowledge and hikmah in business administration academic programs - Zainudin, Dolhadi; Mhd. Sarif, Suhaimi; Ismail, Yusof (Kulliyyah of Economics and Management Sciences IIUM, 2021)
Dolhadi Zainudin Suhaimi Mhd Sarif Yusof Ismail This chapter explores the influence of budi, knowledge and hikmah in business administration academic programs. Budi provides the foundation of virtue and morality before the learning to know in business administration courses. The multidisciplinary nature of business administration requires strong footing in budi and knowledge before gaining hikmah.